Consumers’ Expectation and Perception toward Mobile Telecommunication Usage in Bangladesh - Alam, Md. Ashraful; Roy, Debashish; Akther, Rehana (Asian Business Review, 2016)
Recently telecommunication sector like the mobile phone has made a revolution in the world. For the last few years, it has become part and parcel of our daily life. Business, commerce, and society cannot go out without the use of mobile phone. With the continuous diversification, the use of mobile is not only limited to talking, but its use ranges from using internet, sending messages, listening to music, to organizing various works are comfortably completed in time. City Cell Company introduced the use of mobile phone in Bangladesh in the middle of 1989 .Now with the lapse of time; another five operators have in the market. The mobile operators need to understand well, the perceptions of service quality of customers and their expectations. The study “Consumers’ expectations and perception toward mobile telecommunication usage in Bangladesh” attempts to analyze the gap in telecom sector regarding customers’ expectations and perceptions. It is important to investigate the differences which may provide scope for improvement of mobile service operators. Descriptive analysis, cross tabulation, Chi-square, frequency distribution was used to test the collected data and hypotheses of the research study. The study concludes that, given the severe competition in the business arena where mobile operators have to stay alive and breed by pricing strategy, network facilities, and promotional activities. Telecom companies will have to focus on the reduction of the gap in customer expectations and perceptions about their service quality if they are to race internationally. Hence, mobile operators should continually assess and reassess how customers perceive their services and to implement appropriate corrective action for retaining the existing customers and getting new customers.